Running with a mask? The effect of air pollution on marathon runners` performance - Guo, M.; Fu, S. (Journal of Sports Economics, 2019)
Using a sample of more than 0.3 million marathon runners of 56 race events in China in 2014 and 2015, we estimate the air pollution elasticity of finish time to be 0.041. Our causal identification comes from the exogeneity of air pollution on the race day because runners are required to register for a race a few months in advance and we control for confounding factors. Including individual fixed effects also provides consistent evidence. Our study contributes to the emerging literature on the effect of air pollution on short-run productivity, particularly on the performance of athletes engaging in outdoor sports.